2001
DOI: 10.1590/s1413-86702001000200002
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose adrenocorticotropin test in patients with the Acquired Immunodeficiency Syndrome

Abstract: Adrenocortical insufficiency is a serious complication of AIDS. Usually, integrity of the hypothalamo-pituitary-adrenal (HPA) axis in AIDS patients is assessed by measuring basal cortisol levels and cortisol response to 250 microg of ACTH. Recent studies suggest that a lower ACTH dose increases the sensitivity of the procedure. In the present study, we investigated the prevalence of adrenal hypofunction in AIDS patients using a low-dose ACTH test (1 microg), evaluated the clinical characteristics that might su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…In this study, using a cortisol cutoff level of 400 nmol/l, the prevalence of 27% for hypoadrenalism is higher than 19% reported in a recent Ugandan study [8] and 19% in a Brazilian study [14] . The reasons for our higher prevalence of hypoadrenalism in comparison with the Ugandan study [8] which comprised 113 patients and the Brazilian study [14] which included 63 HIV-positive patients is not obvious.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In this study, using a cortisol cutoff level of 400 nmol/l, the prevalence of 27% for hypoadrenalism is higher than 19% reported in a recent Ugandan study [8] and 19% in a Brazilian study [14] . The reasons for our higher prevalence of hypoadrenalism in comparison with the Ugandan study [8] which comprised 113 patients and the Brazilian study [14] which included 63 HIV-positive patients is not obvious.…”
Section: Discussioncontrasting
confidence: 67%
“…The reasons for our higher prevalence of hypoadrenalism in comparison with the Ugandan study [8] which comprised 113 patients and the Brazilian study [14] which included 63 HIV-positive patients is not obvious. The high prevalence of CMV infection in our patients (n = 66/66) may have contributed to our relatively high prevalence of hypoadrenalism.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…15,16 However, patients with advanced disease may also develop cortisol resistance, leading to clinical signs of adrenal insufficiency in the face of normal or increased basal cortisol levels. Symptomatic and advanced disease in adults can frequently result in diminished response to corticotropin-releasing hormone, adrenocorticotropic hormone (ACTH) deficiency, or primary adrenal insufficiency 4,15,17 ; data in children are scarce.…”
Section: Inflammatory Effectsmentioning
confidence: 99%
“…Some authors have demonstrated similar results with low and standard doses (1 and 250 µg), suggesting that a lower dose of ACTH is enough to diagnose sub clinical adrenal insufficiency 10,21 . Other authors have found a greater frequency of primary adrenal dysfunction in patients with Acquired Immunodeficiency Syndrome using low doses in comparison to other studies that used standard doses 23 . In this study we demonstrated adrenal reserve in all patients, but we don't know if the results would be the same with a low dose of ACTH.…”
Section: Discussionmentioning
confidence: 72%